KONTROL DIRI DAN PERILAKU MEROKOK PADA SISWA SMA - Indra Dwi Setiawan; Octa Reni Setiawati; Sri Maria Puji Lestari (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ABSTRACT: SELF CONTROL AND SMOKING BEHAVIOR IN HIGH SCHOOL STUDENT Smoking behavior appears a lot among adolescents. Smoking behavior is a form of juvenile delinquency related to self-control abilities. This study aims to determine the relationship between self-control and smoking behavior in high school students. The study was conducted on 205 students of SMA Negeri 1 Trimurjo, Central Lampung Regency. The research data were obtained through self-control questionnaires and smoking behavior. Data analysis used Pearson correlation test. The results showed that high school students had moderate self-control and smoking behavior. There is a significant relationship between self-control and smoking behavior in high school students, with low correlation strength and negative correlation direction, which means the higher self-control, the lower one's smoking behavior. The results of this study can be a reference for the school in developing self-control intervention programs to reduce smoking behavior among high school students. Keywords: Self-Control, Smoking Behavior, High School Students Perilaku merokok banyak muncul di kalangan remaja. Perilaku merokok merupakan bentuk kenakalan remaja yang berhubungan dengan kemampuan pengendalian diri. Penelitian ini bertujuan untuk mengetahui hubungan kontrol diri dengan perilaku merokok pada siswa SMA. Penelitian dilakukan terhadap 205 siswa SMA Negeri 1 Trimurjo Kabupaten Lampung Tengah. Data penelitian diperoleh melalui kuesioner kontrol diri dan perilaku merokok. Analisis data menggunakan uji korelasi Pearson. Hasil penelitian menunjukkan siswa SMA memiliki control diri dan perilaku merokok tingkat sedang. Terdapat hubungan bermakna antara kontrol diri dan perilaku merokok pada siswa SMA, dengan kekuatan korelasi rendah dan arah korelasi negatif yaitu semakin tinggi kontrol diri maka semakin rendah perilaku merokok seseorang. Hasil penelitian ini dapat menjadi acuan bagi pihak sekolah dalam mengembangkan program intervensi control diri untuk. mengurangi perilaku merokok siswa SMA. Kata Kunci :Kontrol Diri, Perilaku Merokok, Siswa SMA